Glycogen Synthase Kinase 3 Gene Is Important in Growth and Molting of the Pacific White Shrimp Litopenaeus vannamei - Pang, Ying; Zhang, Xiaojun; Yuan, Jianbo; Zhang, Xiaoxi; Su, Manwen; Li, Fuhua (Frontiers in Marine Science, 2021)
Glycogen synthase kinase 3 (GSK3) is a vital multifunctional molecule that widely distributed in invertebrates and vertebrates. GSK3 is a highly conserved Serine/Threonine (Ser/Thr) protein kinase，which plays an important role in insulin, Wnt and various signaling pathways. In this study, a GSK3 gene were identified in the genome of the Pacific white shrimp, Litopenaeus vannamei, and analyzed its gene structure, phylogeny, and expression profiles. The deduced LvGSK3 protein contains a highly conserved Ser/Thr protein kinases catalytic (S_TKc) domain, the LvGSK3 gene exhibited high expression in different early developmental stages, most adult tissues and pre-molting stages. RNA interference of LvGSK3 significantly retarded the increment of body weight and affected the expressions of molting-related genes compared to control groups. These results will improve our understanding of the conserved structure and functions of the LvGSK3 gene and show potential applications of shrimp growth.